2019
DOI: 10.35121/ijapie201901138
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheological Fluid Finishing of Soft Materials: A Critical Review

Abstract: Magnetorheological Finishing (MRF) is one of the precision finishing processes and recently commercialized method for finishing of various materials like optical glasses, metals, non-metals etc. This method utilizes a suspension consisting of a fluid carrier which can be water or oil, both magnetic and non-magnetic particles and stabilizing agents. Rheological behavior of this mixture of magnetorheological (MR) fluid with abrasives changes under the influence of magnetic field which in turn regulates the finis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Simulation of magnetic flux showed that the shape and size of the ball-end finishing spot varied with the working gap at particular magnetic current. Sharma (2019) critically reviewed MRF, MRAFF, CMMRF, BEMRF finishing process and concluded that BEMRF process is an effective process to obtain high level of surface finish on variety of work pieces. Sharma (2020) reviewed in detail the BEMRF process and concluded that this process can be effectively used for finishing of both magnetic and non-magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation of magnetic flux showed that the shape and size of the ball-end finishing spot varied with the working gap at particular magnetic current. Sharma (2019) critically reviewed MRF, MRAFF, CMMRF, BEMRF finishing process and concluded that BEMRF process is an effective process to obtain high level of surface finish on variety of work pieces. Sharma (2020) reviewed in detail the BEMRF process and concluded that this process can be effectively used for finishing of both magnetic and non-magnetic materials.…”
Section: Introductionmentioning
confidence: 99%